a is first term
d is common difference
n is number of terms
Sn is sum of n terms
Sn = n /2 [2a + (n - 1) d]
S50 = 25 [4 + 49 x 2 ]
S50 = 25[102]
S50 = 2550
2007-11-23 03:49:44
·
answer #1
·
answered by Como 7
·
1⤊
2⤋
1 + 2 + 3 + .... + n = n(n+1)/2
2 + 4 + 6 + 8 + .... + 96 + 98 + 100
= 2(1 + 2 + 3 + 4 + ....+ 48 + 49 + 50)
= 2 * (50*51/2)
= 50*51
= 2550
2007-11-22 20:38:45
·
answer #2
·
answered by gudspeling 7
·
2⤊
0⤋
2 + 4 + 6 + 8 + 10 + 12 + .... upto 50 terms
= 2(1 + 2 + 3 + 4 + 5 + 6 + .... upto 50 terms)
= 2*50*51/2
= 2550 since 1 + 2 + 3 + .... + n = n(n + 1)/2
2007-11-22 20:48:32
·
answer #3
·
answered by sv 7
·
1⤊
0⤋
take the first and the 50th even number add them together =102 divide 50 by 2 = 25 multiply 102 by 25 = 2550.
This is how it works:
100+2 = 102
98+4=102
96+6=102
94+8=102
..... it continues until run out of even numbers, oh and you can't use the same number twice
2007-11-22 21:00:23
·
answer #4
·
answered by Oscar A 2
·
0⤊
1⤋
a(n) = 2 + 2(n - 1)
a(50) = 2 + 2(50 - 1) = 2 + 2(49) = 2 + 98 = 100
using this you get
S(n) = (50/2)(2 + 100) = 25(102) = 2550
2007-11-22 21:33:11
·
answer #5
·
answered by Sherman81 6
·
0⤊
1⤋
2+4+6+8 ... t(50)
Sn = n/2(2a + (n-1)d
Sn = Sum
n = number of terms = 50
a = initial term = 2 (first even number)
d= difference between terms = 2 (4-2 or 6-4)
Sn = 50/2(2(2) + (50-1)2)
= 25(4+198)
25(202) = 5050
2007-11-22 21:02:46
·
answer #6
·
answered by A Little Sarcasm Helps 5
·
0⤊
1⤋